ANALISIS TINGKAT PENGEMBALIAN INVESTASI PADA EQUITY SECURITIES MELALUI RASIO PROFITABILITAS, LIKUIDITAS DAN HUTANG PADA PERUSAHAAN PERBANKAN DI BEI PERIODE 2015-2017 - Dinda Oktaviani; Mohammad Amin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determine the effect of Return On Investment, Current Ratio and Debt to Equity Ratio on return on investment which is calculated using the Dividend Payout Ratio for banking companies listed on the Stock Exchange for the period 2015-2017. The population in this study were banking companies listed on the Stock Exchange in the period 2015-2017, which amounted to 14 banking companies that were taken using purposive sampling technique, namely the selection of sample members based on certain criteria. The data collection method used is the documentation method, namely by recording or documenting the data listed in the annual report on (IDX). The data analysis technique used in this study is multiple regression, classic assumption test. The result of the study prove that partially return on investment and current ratio have a positive effect on dividend payout ratio, while the debt to equity ratio does not significantly influence the dividend payout ratio. Simultaneously the return on investment, current ratio, and debt to equity ratio significantly influence the dividend payout ratio.Keywords: Return On Investment (ROI), Current Ratio (CR), Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR)